Performance Evaluation of Bari Inclined Plate Planter for Lentil Cultivation (Journal of Environmental Science and Natural Resources, 2018)
A field trial was carried out at Farm Machinery Technology Dissemination (FMTD) project site, Sujanagor, Pabna to test performance of planting methods with Bangladesh Agricultural Research Institute (BARI) inclined plate planter, BARI Bed planter over conventional manual planting method for sowing lentil during 2014-15. Mechanical planting method with BARI Inclined Plate Planter showed highest yield (1.67 tha-1) whereas it was obtained1.54 tha-1 for bed planter and 1.41 tha-1 for conventional manual planting method. Planting methods exhibited non significant response on yield attributes like number of plants population, plant height, seed pod-1, dry weight of 10 plants and weight of 100 seeds. However, highest no. of pod plant-1 (168.83), primary branch (6.77) and secondary branch (33.67) was obtained from planting by IPP and these three parameters were shown lowest value (70.20, 3.5 and 11.8 respectively) in manual seeding methods. Total Cost of complete land preparation and planting was exhibited lowest for seed sowing with BARI Inclined Plate Planter (2016 Tk. ha-1) and it was 2727 Tk. ha-1 for BARI bed planter and highest for conventional manual seed sowing method (4433 Tk.ha-1).J. Environ. Sci. & Natural Resources, 10(2): 39-44 2017